Dermoscopic appearance of an amelanotic mucosal melanoma - Andreas Blum; Ulrike Beck-Zoul; Laura Held; Sylvie Haase (Mattioli1885, 2016)
Background: Hypomelanotic or amelanotic melanomas are challenging to identify, especially at mucosal sites. The dermoscopic clues to the diagnosis of mucosal melanomas have been reported to be structureless zones with the presence of blue, gray, or white colors. Case: A female in her seventies noted a new lesion on the inside of her right labia that first appeared two months prior. Her past medical history was significant for rheumatoid arthritis requiring ongoing treatment with methotrexate for 20 years and adalimumab for 10 years. After no response to two weeks of local treatment for suspected herpes simplex infection, her gynecologist performed a skin biopsy. Based on the histopathological diagnosis of an amelanotic melanoma (Breslow thickness of 1.3 mm) the patient was referred to dermatology for further assessment. Polarized dermoscopy revealed a distinct asymmetric, sharply demarcated homogenous white papule (4 x 5 mm) as well as polymorphous vessels. Conclusion: Dermoscopy may aid in the diagnosis of amelanotic mucosal melanomas. Our case revealed a structureless white area and polymorphous vessels. Additional clues to the diagnosis were the advanced age of the patient and the clinical presentation of a new lesion.